The dynamics of superposition of volterra and permuted volterra quadratic stochastic operators: The dynamics of superposition of volterra and permuted volterra quadratic stochastic operators - Jamilov, U.U.; Aralova, K.A. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
The concept of a quadratic stochastic operator and its application in a biological context were first established by Bernstein in [1]. Since then, the theory of quadratic stochastic operators has been further deepened motivated by their frequent occurrence in mathematical models of genetics, where quadratic stochastic operators serve as a tool for the study of dynamical properties and modelling; see e.g. [2,3,4].